Revival of Pilgrimage Tourism at the Crossroads of the Great Silk Road (By the Example of the Tashkent Oasis) - Jumaeva Shoira Berdiyarovna; Juraev Arslon Ashur ugli (Zien Journals, 2023)
In the article, the author analyzed the possibilities of pilgrimage tourism in the Tashkent region, and the topic was highlighted on the example of one of the places of pilgrimage centers in the Machit Ali region, located in the Parkent district.
Keywords: Tashkent oasis; Great Silk Road; tourism